Hot dipping post treatment for improved efficiency in micro patterned semi-transparent perovskite solar cells. Issue 46 (14th November 2018) - Rai, Monika; Rahmany, Stav; Lim, Swee Sien; Magdassi, Shlomo; Wong, Lydia Helena; Etgar, Lioz
Abstract : Perovskite solar cells have emerged as a new semi-transparent PV technology for urban infrastructures that demands an explicit trade-off between power conversion efficiency (PCE) and average visible transparency (AVT) which can be adjusted by various modifications in the absorber layer. Abstract : Perovskite solar cells have emerged as a new semi-transparent PV technology for urban infrastructures that demands an explicit trade-off between power conversion efficiency (PCE) and average visible transparency (AVT) which can be adjusted by various modifications in the absorber layer. Here, we introduce a scalable and facile "one and a half" step deposition route for mixed cation perovskites patterned in a sub-micron sized grid structure for semi-transparent solar cells. The initial perovskite phase is formed in one step using a grid pattern, while the additional step involves dipping of the pre-deposited perovskite grid in a hot solution of formamidinium iodide (FAI) in isopropanol (IPA). Detailed analysis suggests that the additional step increases pore filling, crystal quality, and grain size and lowers the content of residual PbI2 as well as reveals improved photo physical properties. An average PCE ∼10% with an AVT of 28% is attained with a gold contact for the champion semi-transparent solar cell. The proposed deposition route can be generalized for all other types of perovskite based devices to yield better efficiency.